2021
DOI: 10.1111/hae.14368
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurements of haemophilic joint tissues by point‐of‐care musculoskeletal ultrasound: Associations with clinical and functional joint outcome parameters

Abstract: Background Painful arthropathy is a long‐term complication in patients with hemophilia (PWH), affecting mobility and quality of life. A major barrier for the appraisal of joint health is the absence of point‐of‐care (POC) imaging modalities to promptly identify and manage arthropathic changes. Accordingly, we developed the Joint tissue Activity and Damage Exam (JADE) POC musculoskeletal ultrasound (MSKUS) protocol. JADE is validated for haemophilic joint tissue recognition with high intra/inter‐rater and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Ankles were most affected and treated with PT, followed by knees and elbows. Of interest, we reported previously that the number of joints without measurable cartilage in ankles was much higher compared to elbows and knees when applying JADE measurements to the same cohort of PwH [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankles were most affected and treated with PT, followed by knees and elbows. Of interest, we reported previously that the number of joints without measurable cartilage in ankles was much higher compared to elbows and knees when applying JADE measurements to the same cohort of PwH [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The JADE protocol has been validated by Outcomes Measures in Rheumatology (OMERACT) guidelines [ 35 ] on the tissue discrimination level [ 35 ], and has demonstrated high intra/inter-rater and inter-operator reliability [ 29 , 36 , 37 ]. Also, the direct tissue measurements correlate well with clinical and functional parameters used to evaluate PwH [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Denver Score 13 and International Prophylaxis Study Group 14 ) and ultrasound (e.g. Haemophilia Early Arthropathy Detection with Ultrasound [HEAD-US], 15 Joint Tissue Activity and Damage Exam [JADE], 16,17 and Universal Simplified Ultrasound (US-US) protocol 18 ); for activities and participation, the Haemophilia Activities List (HAL) 19 and the Functional Independence Score in Haemophilia (FISH). 20 Haemophilic arthropathy involves complex processes that need to be incorporated into assessments for joint health throughout the disease course of haemophilia.…”
Section: Ly T Ic E N Z Y M E Smentioning
confidence: 99%
“…Physical examination may detect significant joint changes, whereas ultrasound can identify abnormalities that may be missed by physical examination alone 66 . HJHS clinical measures also correlate with intra‐articular ultrasound measurements using JADE in patients with haemophilia 17 . A systematic review of 98 study reports found that the HJHS is the most extensively studied joint assessment tool and is used in clinical practice to assess children and young adults receiving intensive treatment 67 .…”
Section: Relationship Between Assessments For Functional Ability and ...mentioning
confidence: 99%
See 1 more Smart Citation